Developmental Stages and Seasonal History of Pauropsylla tuberculata Crawford on Alstonia scholaris (L.) R. Br. - Singh, Jaideep; Sangha, K. S. (Indian Forester, 2018)
The studies on the developmental stages and seasonal history of leaf gall insect, P. tuberculata Crawford, which forms galls on Alstonia scholaris(L.) R. Br. was studied in lab and field at the Biocontrol Laboratories, Punjab Agricultural University, Ludhiana during 2015-16. Pauropsylla tuberculata has five nymphal instars in its life cycle. The mature insect is colorful, winged and with bulging eyes and the female is larger than male in size. Maximum population of galls/leaf, galls/pod, psyllids emerged from leaf galls and psyllids emerged from pod galls were recorded in month of July 2015 at different locations of Punjab Agricultural University, Ludhiana and Guru Angad Dev Veterinary and Animal Sciences, Ludhiana. Peak activity period was observed from July 2015 to September 2015 and the minimum activity was observed from December 2015 to February 2016. Further, total number of galls/leaf, galls/pod, psyllids emerged from leaf galls and psyllids emerged from pod galls were positively correlated with maximum temperature, minimum temperature and rainfall but negatively correlated with relative humidity.